Desmoid Tumor After a Minimally Invasive Atrial Septal Defect Closure in an Adolescent. (September 2016) - Amaral, Fernando; Jacob, Maria Fernanda Balthazar; Manso, Paulo Henrique; Camperoni, Luis Eduardo R.; Vicente, Walter V. A.; Schreiber, Christian
The surgical closure of secundum atrial septal defect (ASD) is frequently performed. The minimally invasive approach, currently adopted by many centers as a way to preserve aesthetic appearance, particularly in female patients, seems to be safe. We describe the case of an adolescent who developed a desmoid tumor soon after a minimally invasive operation for surgical closure of a secundum ASD.